A modified iterative algorithm for nonexpansive mappings Youli Yu ∗, Ching-Feng Wen †, Abstract A modified iterative algorithm is presented based on the semi-implicit midpoint rule. Strong convergence analysis is demonstrated. Our method gives a unified framework related to the implicit midpoint rule. Our results improve and extend the corresponding results in the literature. Keywords: nonexpansive mapping; implicit midpoint rule; fixed point. 2010 Mathematics Subject Classification: 47J25; 47N20; 34G20; 65J15. 1 Introduction The purpose of the paper is to construct iterative methods for finding the fixed points of nonexpansive mappings. Fixed point methods for nonexpansive mappings have been studied extensively by many researchers due to its applications in engineering and natural science. Especially, the following fixed point methods have attracted so much attention. Browder’s method ([1]): for fixed u ∈ C, xt = tu + (1 − t)T xt , where t ∈ (0, 1). Mann’s method ([2]): xn+1 = αn xn + (1 − αn )T xn , n ≥ 0, where αn ∈ (0, 1). Ishikawa’s methd ([3]): yn = αn xn + (1 − αn )T xn , xn+1 = βn xn + (1 − βn )T yn , n ≥ 0, where αn and βn are in (0, 1). Halpern’s method ([4]): xn+1 = αn u + (1 − αn )T xn , n ≥ 0, ∗ School of Mathematics and Information Engineering, Taizhou University, Linhai 317000, China. e-mail: yuyouli@tzc.edu.cn † Corresponding Author, Center for Fundamental Science, and Research Center for Nonlinear Analysis and Optimizatio, Kaohsiung Medical University, Kaohsiung, 807, Taiwan. e-mail: cfwen@kmu.edu.tw 1 where u ∈ C is a fixed point and αn ∈ (0, 1). Moudafi’s viscosity method ([5]) xn+1 = αn Q(xn ) + (1 − αn )T xn , n ≥ 0, where Q : C → C is a contraction and αn ∈ (0, 1). Modified Mann’s method ([6]): yn = αn xn + (1 − αn )T xn , xn+1 = βn u + (1 − βn )yn , n ≥ 0. Many researchers demonstrated the convergence results of the above methods and their variant forms. Related references, please refer to [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 33]. Very recently, in [27] and [28], the authors presented the following semi-implicit midpoint rule for nonexpansive mappings: ( xn+1 = (1 − αn )xn + αn T ) xn + xn+1 , n ≥ 0, 2 (1.1) and ( xn+1 = αn Q(xn ) + (1 − αn )T ) xn + xn+1 , n ≥ 0, 2 (1.2) where αn ∈ (0, 1) and Q is a contraction. Further, Yao, Shahzad and Liou [29] introduced the following semi-implicit midpoint method: ( xn+1 ) xn + xn+1 = αn Q(xn ) + βn xn + γn T , n ≥ 0. 2 (1.3) Motivated and inspired by the above works, the purpose of the paper is to construct the following unified iterative algorithm for finding the fixed points of nonexpansive mappings xn+1 = αn Q(xn ) + βn xn + γn T (δn xn + (1 − δn )xn+1 ), n ≥ 0. We prove that the above algorithm converges strongly to a fixed point of nonexpansive mappings T . 2 Preliminaries Let H be a real Hilbert space with inner product ⟨·, ·⟩ and norm ∥ · ∥, respectively. Let C be a nonempty closed convex subset of H. A mapping T : C → C is said to be nonexpansive if ∥T x − T y∥ ≤ ∥x − y∥ for all x, y ∈ C. We use F ix(T ) to denote the set of fixed points of T . A mapping Q : C → C is said to be contractive if there exists a constant α ∈ (0, 1) such that ∥Q(x) − Q(y)∥ ≤ α∥x − y∥ for all x, y ∈ C. In this case, Q is called α-contraction. 2 Lemma 2.1. ([30]) Let C be a nonempty closed convex subset of a Hilbert space H, and let T : C → C be a nonexpansive mapping with F ix(T ) ̸= ∅. Assume that {yn } is a sequence in C such that yn ⇀ x† and (I − T )yn → 0. Then x† ∈ F ix(T ). Lemma 2.2. ([31]) Let {xn } and {yn } be bounded sequences in a Banach space E and {βn } be a sequence in [0, 1] with 0 < lim inf n→∞ βn ≤ lim supn→∞ βn < 1. Suppose that xn+1 = (1 − βn )xn + βn zn for all n ≥ 0 and lim supn→∞ (∥zn+1 − zn ∥ − ∥xn+1 − xn ∥) ≤ 0. Then limn→∞ ∥zn − xn ∥ = 0. Lemma 2.3. ([32]) Let {an }n∈N be a sequence of non-negative real numbers satisfying the following relation: an+1 ≤ (1 − αn )an + αn σn + δn , where (i) {αn }n∈N ⊂ [0, 1] and ∑∞ n=1 n ≥ 0, αn = ∞; (ii) lim supn→∞ σn ≤ 0; ∑∞ (iii) n=1 δn < ∞. Then limn→∞ an = 0. 3 Main results Throughout, we assume that H is a real Hilbert space and C ⊂ H is a nonempty closed convex set. Let T : C → C be a nonexpansive mapping with its fixed points set being nonempty, that is, F ix(T ) ̸= ∅. Let Q : C → C be an α-contraction. Now, we firstly present the following unified iterative algorithm. Algorithm 3.1. For given x0 ∈ C arbitrarily, let the sequence {xn } be generated iteratively by the manner xn+1 = αn Q(xn ) + βn xn + γn T (δn xn + (1 − δn )xn+1 ), n ≥ 0, (3.1) where {αn } ⊂ (0, 1), {βn } ⊂ [0, 1), {γn } ⊂ (0, 1) and {δn } ⊂ [κ1 , κ2 ] ⊂ (0, 1) are four sequences satisfying αn + βn + γn = 1 for all n ≥ 0. Remark 3.2. (3.1) is well-defined. As a matter of fact, for fixed u ∈ C, we can define a mapping x 7→ Tu x := αQ(u) + βu + γT (δu + (1 − δ)x), ∀x ∈ C. Then, we have ∥Tu x − Tu y∥ = γ∥T (δu + (1 − δ)x) − T (δu + (1 − δ)y)∥ ≤ (1 − δ)γ∥x − y∥. This means Tu is a contraction with coefficient (1−δ)γ ∈ (0, 1). Hence, Algorithm 3.1 is well-defined. 3 Next, we show the boundedness of the sequence {xn }. Proposition 3.3. The sequence {xn } generated by (3.1) is bounded. Proof. Let z ♯ ∈ F ix(T ). From (3.1), we get ∥xn+1 − z ♯ ∥ = ∥αn (Q(xn ) − Q(z ♯ )) + αn (Q(z ♯ ) − z ♯ ) + βn (xn − z ♯ ) + γn (T (δn xn + (1 − δn )xn+1 ) − z ♯ )∥ ≤ αn ∥Q(xn ) − Q(z ♯ )∥ + αn ∥Q(z ♯ ) − z ♯ ∥ + βn ∥xn − z ♯ ∥ + γn ∥T (δn xn + (1 − δn )xn+1 ) − z ♯ ∥ ≤ αn α∥xn − z ♯ ∥ + αn ∥Q(z ♯ ) − z ♯ ∥ + βn ∥xn − z ♯ ∥ + γn δn ∥xn − z ♯ ∥ + γn (1 − δn )∥xn+1 − z ♯ ∥. From the last inequality, we obtain αn α + βn + γn δn αn ∥xn − z ♯ ∥ + ∥Q(z ♯ ) − z ♯ ∥ 1 − γn (1 − δn ) 1 − γn (1 − δn ) [ ] (1 − α)αn (1 − α)αn 1 = 1− ∥xn − z ♯ ∥ + ∥Q(z ♯ ) − z ♯ ∥ 1 − γn (1 − δn ) 1 − γn (1 − δn ) 1 − α 1 ≤ max{∥xn − z ♯ ∥, ∥Q(z ♯ ) − z ♯ ∥}. 1−α ∥xn+1 − z ♯ ∥ ≤ By induction, we deduce ∥xn − z ♯ ∥ ≤ max{∥x0 − z ♯ ∥, 1 ∥Q(z ♯ ) − z ♯ ∥}. 1−α This indicates that {xn } is bounded. This completes the proof. Next, we state the following theorem Theorem 3.4. Assume {αn }, {βn } and {γn } satisfy the conditions (C1) : limn→∞ αn = 0; (C2) : ∑∞ n=0 αn = ∞; (C3) : limn→∞ |αn −αn−1 | α2n = 0; (C4) : limn→∞ |βn −βn−1 | α2n = 0; (C5) : lim inf n→∞ γn > 0. Then the sequence {xn } generated by (3.1) converges strongly to q = PF ix(T ) Q(q). 4 Proof. Set zn = αn 1−βn Q(zn ) + (1 − αn 1−βn )T zn for all n. By [8], we have that the sequence {zn } converges strongly to q = PF ix(T ) Q(q) provided limn→∞ αn = 0. Note that the sequences {xn } and {zn } are all bounded. We can rewrite yn as zn = αn Q(zn ) + βn zn + γn T zn , n ≥ 0. First, we note that ∥xn+1 − zn ∥ = ∥αn (Q(xn ) − Q(zn )) + βn (xn − zn ) + γn (T (δn xn + (1 − δ)xn+1 ) − T zn )∥ ≤ αn α∥xn − zn ∥ + βn ∥xn − zn ∥ + γn δn ∥xn − zn ∥ + γn (1 − δn )∥xn+1 − zn ∥. It follows that [ ] (1 − α)αn ∥xn+1 − zn ∥ ≤ 1 − ∥xn − zn ∥ 1 − γn (1 − δn ) [ ] (1 − α)αn ≤ 1− ∥xn − zn−1 ∥ + ∥zn − zn−1 ∥. 1 − γn (1 − δn ) It is easily seen that if ∑∞ n=0 αn = ∞ and limn→∞ ∥zn −zn−1 ∥ αn = 0, then we get limn→∞ ∥xn+1 −zn ∥ = 0 by Lemma 2.3. Consequently, xn → q = PF ix(T ) Q(q) provided limn→∞ αn = 0. Next, we estimate ∥zn −zn−1 ∥ . αn As a matter of fact, we have ∥zn − zn−1 ∥ = ∥αn (Q(zn ) − Q(zn−1 )) + (αn − αn−1 )Q(zn−1 ) + βn (zn − zn−1 ) + (βn − βn−1 )zn−1 + γn (T zn − T zn−1 ) + (γn − γn−1 )T zn−1 ∥ ≤ (ααn + βn + γn )∥zn − zn−1 ∥ + |αn − αn−1 |∥Q(zn−1 )∥ + |βn − βn−1 |∥zn−1 ∥ + |γn − γn−1 |∥T zn−1 ∥. Hence, |βn − βn−1 | ∥zn − zn−1 ∥ |αn − αn−1 | (∥Q(zn−1 )∥ + ∥T zn−1 ∥) + (∥zn−1 ∥ + ∥T zn−1 ∥). ≤ 2 αn (1 − α)αn (1 − α)αn2 Since limn→∞ |αn −αn−1 | α2n = limn→∞ |βn −βn−1 | α2n = 0, we derive that limn→∞ ∥zn −zn−1 ∥ αn = 0. Therefore, limn→∞ ∥xn+1 − zn ∥ = 0 and thus xn → q = PF ix(T ) Q(q). This completes the proof. Theorem 3.5. Assume {αn } satisfies (C1) and (C2), {βn } and {δn } satisfies (C1) : limn→∞ αn = 0; (C2) : ∑∞ n=0 αn = ∞; (C6) : 0 < lim inf n→∞ βn ≤ lim supn→∞ βn < 1; (C7) : limn→∞ (βn+1 − βn ) = 0; (C8) : limn→∞ (δn+1 − δn ) = 0. 5 Then the sequence {xn } generated by (3.1) converges strongly to q = PF ix(T ) Q(q). Proof. From Proposition 3.3, we have can choose a constant M such that )( {( )} 3 3 sup + ∥Q(xn )∥ + ∥T (δn xn + (1 − δn )xn+1 )∥ + ∥xn ∥ ≤ M. 1 − βn 1 − γn n Set yn = xn+1 −βn xn 1−βn for all n ≥ 0. Thus, we have xn+2 − βn+1 xn+1 xn+1 − βn xn − 1 − βn+1 1 − βn αn+1 Q(xn+1 ) + (1 − αn+1 − βn+1 )T (δn+1 xn+1 + (1 − δn+1 )xn+2 ) = 1 − βn+1 αn Q(xn ) + (1 − αn − βn )T (δn xn + (1 − δn )xn+1 ) − 1 − βn αn+1 (Q(xn+1 ) − Q(xn )) = 1 − βn+1 1 − αn+1 − βn+1 + (T (δn+1 xn+1 + (1 − δn+1 )xn+2 ) − T (δn xn + (1 − δn )xn+1 )) 1 − βn+1 ( ) αn+1 αn + − (Q(xn ) − T (δn xn + (1 − δn )xn+1 )). 1 − βn+1 1 − βn yn+1 − yn = It follows that ( ) αn+1 αn ∥yn+1 − yn ∥ ≤ + ∥Q(xn ) − T (δn xn + (1 − δn )xn+1 )∥ 1 − βn+1 1 − βn 1 − αn+1 − βn+1 (δn+1 ∥xn+1 − xn ∥ + (1 − δn+1 )∥xn+2 − xn+1 ∥) + 1 − βn+1 1 − αn+1 − βn+1 + |δn+1 − δn |(∥xn ∥ + ∥xn+1 ∥) 1 − βn+1 ααn+1 + ∥xn+1 − xn ∥. 1 − βn+1 From (3.1), we have ∥xn+2 − xn+1 ∥ = ∥αn+1 (Q(xn+1 ) − Q(xn )) + (αn+1 − αn )Q(xn ) + βn+1 (xn+1 − xn ) + (βn+1 − βn )(xn − T (δn xn + (1 − δn )xn+1 )) + γn+1 (T (δn+1 xn+1 + (1 − δn+1 )xn+2 ) − T (δn xn + (1 − δn )xn+1 )) + (αn − αn+1 )T (δn xn + (1 − δn )xn+1 )∥ ≤ ααn+1 ∥xn+1 − xn ∥ + (αn+1 + αn )∥Q(xn )∥ + βn+1 ∥xn+1 − xn ∥ + γn+1 (δn+1 ∥xn+1 − xn ∥ + (1 − δn+1 )∥xn+2 − xn+1 ∥) + γn+1 |δn+1 − δn |(∥xn ∥ + ∥xn+1 ∥) + (αn + αn+1 )∥T (δn xn + (1 − δn )xn+1 )∥ + |βn+1 − βn |∥xn − T (δn xn + (1 − δn )xn+1 )∥. 6 (3.2) It follows that [ ∥xn+2 − xn+1 ∥ ≤ 1 − ] (1 − α)αn+1 ∥xn+1 − xn ∥ 1 − γn+1 (1 − δn+1 ) αn+1 + αn + (∥Q(xn )∥ + ∥T (δn xn + (1 − δn )xn+1 )∥) 1 − γn+1 (1 − δn+1 ) (3.3) |βn+1 − βn | + |δn+1 − δn | + (∥xn − T (δn xn + (1 − δn )xn+1 )∥ + ∥xn ∥ + ∥xn+1 ∥) 1 − γn+1 (1 − δn+1 ) ≤ ∥xn+1 − xn ∥ + M (αn + αn+1 + |βn+1 − βn | + |δn+1 − δn |). Substitute (3.3) into (3.2) to get [ ] (1 − α)αn+1 ∥yn+1 − yn ∥ ≤ 1 − ∥xn+1 − xn ∥ + 3M (αn+1 + αn + |βn+1 − βn | + |δn+1 − δn |). 1 − βn+1 Hence, lim sup(∥yn+1 − yn ∥ − ∥xn+1 − xn ∥) ≤ 0. n→∞ This together with Lemma 2.2 implies that lim ∥yn − xn ∥ = 0. n→∞ Note that yn − xn = xn+1 − xn . 1 − βn So, lim ∥xn+1 − xn ∥ = 0. n→∞ (3.4) Again, from (3.1), we have ∥xn − T xn ∥ ≤ ∥xn − xn+1 ∥ + ∥xn+1 − T xn ∥ ≤ ∥xn − xn+1 ∥ + αn ∥Q(xn ) − T xn ∥ + βn ∥xn − T xn ∥ + γn (1 − δn )∥xn − xn+1 ∥. It follows that ∥xn − T xn ∥ ≤ αn 1 + γn (1 − δn ) ∥Q(xn ) − T xn ∥ + ∥xn+1 − xn ∥. 1 − βn 1 − βn This together with (C1) and (3.4) imply that lim ∥xn − T xn ∥ = 0 (3.5) lim sup⟨q − Q(q), q − xn ⟩ ≤ 0, (3.6) n→∞ Next, we prove that n→∞ 7 where q ∈ F ix(T ) is the unique fixed point of the contraction PF ix(T ) Q, that is, q = PF ix(T ) Q(q). Since {xn } is bounded, there exists a subsequence {xni } of {xn } such that {xni } converges weakly to a point x̆ and lim sup⟨PF ix(T ) Q(q) − Q(q), PF ix(T ) Q(q) − xn ⟩ n→∞ = lim ⟨PF ix(T ) Q(q) − Q(q), PF ix(T ) Q(q) − xni ⟩. (3.7) i→∞ By Lemma 2.1 and (3.5), we deduce x̆ ∈ F ix(T ). Therefore, lim sup⟨PF ix(T ) Q(q) − Q(q), PF ix(T ) Q(q) − xn ⟩ n→∞ = lim ⟨PF ix(T ) Q(q) − Q(q), PF ix(T ) Q(q) − xni ⟩ i→∞ = ⟨PF ix(T ) Q(q) − Q(q), PF ix(T ) Q(q) − x̆⟩ ≤ 0. Finally, we prove that xn → q. From (3.1), we have ∥xn+1 − q∥2 = αn ⟨Q(xn ) − Q(q), xn+1 − q⟩ + αn ⟨Q(q) − q, xn+1 − q⟩ + γn ⟨T (δn xn + (1 − δn )xn+1 ) − q, xn+1 − q⟩ + βn ⟨xn − q, xn+1 − q⟩ ≤ αn α∥xn − q∥∥xn+1 − q∥ + αn ⟨Q(q) − q, xn+1 − q⟩ + γn (δn ∥xn − q∥ + (1 − δn )∥xn+1 − q∥)∥xn+1 − q∥ + βn ∥xn − q∥∥xn+1 − q∥ 1 + γn (1 − δn ) − (1 − α)αn 1 − γn (1 − δn ) − (1 − α)αn ∥xn − q∥2 + ∥xn+1 − q∥2 ≤ 2 2 + αn ⟨Q(q) − q, xn+1 − q⟩. It follows that [ ] 2(1 − α)αn ∥xn+1 − q∥ ≤ 1 − ∥xn − q∥2 1 − γn (1 − δn ) + (1 − α)αn 2αn + ⟨Q(q) − q, xn+1 − q⟩. 1 − γn (1 − δn ) + (1 − α)αn 2 (3.8) Applying Lemma 2.3 and (3.6) to (3.8) to deduce that xn → q. This completes the proof. Acknowledgments The research of the send author was partially supported by the grant MOST 104-2115-M-037-001 and the grant from Research Center for Nonlinear Analysis and Optimization, Kaohsiung Medical University, Taiwan. 8 References [1] F. E. Browder, Convergence of approximation to fixed points of nonexpansive nonlinear mappings in Hilbert spaces, Arch. Rational Mech. Anal., 24 (1967), 82–90. 1 [2] W. R. Mann, Mean value methods in iteration, Proc. Amer. Math. Soc., 4 (1953), 506–510. 1 [3] S. Ishikawa, Fixed points by a new iteration method, Proc. Amer. Math. Soc., 44 (1974), 147– 150. 1 [4] B. Halpern, Fixed points of nonexpanding maps, Bull. Am. Math. Soc., 73 (1967), 591–597. 1 [5] A. Moudafi, Viscosity approximation methods for fixed-points problems, J. Math. Anal. Appl., 241 (2000), 46–55. 1 [6] T. H. Kim, H. K. Xu, Strong convergence of modified Mann iterations, Nonlinear Anal., 61 (2005), 51C-60. 1 [7] Y. Yao, R. Chen, J.C. Yao, Strong convergence and certain control conditions for modified Mann iteration, Nonlinear Anal., 68 (2008), 1687–1693. 1 [8] H. K. Xu, Viscosity approximation methods for nonexpansive mappings, J. Math. Anal. Appl., 298 (2004), 279–291. 1, 3 [9] Y. Yao, N, Shahzad, New methods with perturbations for nonexpansive mappings in Hilbert spaces, Fixed Point Theory Appl., 2011 (2011), 9 pages. 1 [10] Y. Yao, M. A. Noor, Y. C. Liou, S.M. Kang, Iterative algorithms for general multivalued variational inequalities, Abstract Appl. Anal., 2012 (2012), 10 pages. 1 [11] Y. Yao, A general iterative method for a finite family of nonexpansive mappings, Nonlinear Anal., 66 (2007), 2676–2687. 1 [12] Y. Yao, Y. J. Cho, Y. C. Liou, Iterative algorithms for variational inclusions, mixed equilibrium problems and fixed point problems approach to optimization problems, Central European J. Math., 9 (2011), 640–656. 1 [13] Y. Yao, Y. J. Cho, Y. C. Liou, Iterative algorithms for hierarchical fixed points problems and variational inequalities, Math. Comput. Modelling, 52 (2010), 1697–1705. 1 [14] Y. Yao, H. K Xu, Iterative methods for finding minimum-norm fixed points of nonexpansive mappings with applications, Optim., 60 (2011), 645–658. 1 9 [15] S. S. Chang, Viscosity approximation methods for a finite family of nonexpansive mappings in Banach spaces, J Math Anal Appl., 323 (2006), 1402–1416. 1 [16] H. H. Bauschke, The approximation of fixed points of compositions of nonexpansive mappings in Hilbert space, J Math Anal Appl., 202 (1996), 150–159. 1 [17] K. Shimoji, W. Takahashi, Strong convergence to common fixed points of infinite nonex-pansive mappings and applications, Taiwanese J Math., 5 (2001), 387–404. 1 [18] Y. Yao, Y.C. Liou, G. Marino, A hybrid algorithm for pseudo-contractive mappings, Nonlinear Anal., 71 (2009), 4997–5002. 1 [19] C. H. Morales, J. S. Jung, Convergence of paths for pseudo-contractive mappings in Banach spaces, Proc. Amer. Math. Soc., 128 (2000), 3411–3419. 1 [20] L. C. Ceng, A. Petrusel, J. C. Yao, Strong Convergence of modified implicit iterative algorithms with perturbed mappings for continuous pseudocontractive mappings, Appl. Math. Comput., 209 (2009), 162–176. 1 [21] H. Zegeye, N. Shahzad, Viscosity approximation methods for a common fixed point of finite family of nonexpansive mappings, Appl. Math. Comput., 191 (2007), 155–163. 1 [22] A. Petrusel, J.C. Yao, Viscosity approximation to common fixed points of families of nonexpansive mappings with generalized contractions mappings, Nonlinear Anal., 69 (2008), 1100C-1111. 1 [23] C. E. Chidume, C. O. Chidume, Iterative approximation of fixed points of nonexpansive mappings, J. Math. Anal. Appl., 318 (2006), 288–295. 1 [24] Y. J. Cho, X. Qin, Convergence of a general iterative method for nonexpansive mappings in Hilbert spaces, J. Comput. Appl. Math., 228 (2009), 458–465. 1 [25] F. Cianciaruso, G. Marino, L. Muglia, Y. Yao, on a two-steps algorithm for hierarchical fixed points problems and variational inequalities, J. Inequalities Appl., 2009 (2009), 13 pages. 1 [26] F. Cianciaruso, G. Marino, L. Muglia, Y. Yao, A hybrid projection algorithm for finding solutions of mixed equilibrium problem and variational inequality problem, Fixed Point Theory Appl., 2010 (2010), 19 pages. 1 [27] M. A. Alghamdi, M. A. Alghamdi, N. Shahzad, H. K. Xu, The implicit midpoint rule for nonexpansive mappings, Fixed Point Theory Appl., 2014 (2014), 9 pages. 1 10 [28] H. K. Xu, M. A. Alghamdi, N. Shahzad, The viscosity technique for the implicit midpoint rule of nonexpansive mappings in Hilbert spaces, Fixed Point Theory Appl., 2015 (2015), 12 pages. 1 [29] Y. Yao, N. Shahzad, Y.C. Liou, Modified semi-implicit midpoint rule for nonexpansive mappings, Fixed Point Theory Appl., 2015 (2015), 15 pages. 1 [30] K. Goebel, W. A. Kirk, Topics in metric fixed point theory, Cambridge University Press, Cambridge, (1990). 2.1 [31] T. Suzuki, Strong convergence theorems for infinite families of nonexpansive mappings in general Banach spaces, Fixed Point Theory Appl., 2005 (2005), 103–123. 2.2 [32] H. K. Xu, Iterative algorithms for nonlinear operators, J. Lond. Math. Soc., 66 (2002), 240–256. 2.3 [33] Y. Yao, M. Postolache, Y.C. Liou Z. Yao, Construction algorithms for a class of monotone variational inequalities, Optim. Lett., in press. 1 11